IMPLEMENTASI TAX PLANNING DALAM UPAYA PENGHEMATAN PAJAK PENGHASILAN (PPh) BADAN (Studi Pada Koperasi Wanita Serba Usaha “Setia Budi Wanita” Jawa Timur) - Tyas Titi Alkasari (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
One mainstay of current Indonesian government revenue is tax revenue, especially income tax. For a company or corporation, the tax is a major burden that would reduce net income, so it is necessary to do tax planning in an effort to minimize the tax burden and improve the performance of the company. Tax planning is legal efforts undertaken taxpayer by utilizing things that are not organized or existing under the Act and Regulations Taxation. This study was conducted using quantitative descriptive research with case study approach. The results of this study indicate the condition of taxation on Women's Cooperative Business Solutions Business